Medicine Between Ethics and Scientific Progress: How Much Ethics Needs Medicine, how much ethics can it afford? Some Considerations from Patent Law Perspectives - Straus, Joseph (Medicine, Law & Society, 2015)
The progress of medicine is heavily dependent on the progress of science and technology, which in turn depend on costly and risky investment in research and development. In this contribution, based on some concrete examples, new scientific achievements are presented as basis of modern medicine and source of ethical concerns. Addressed are also the role of scientists in coping with safety in ethical concerns as regards hazards of new technologies, costs of R&D investment in drug development and the role of patents in this context. In some detail the legal situation existing at an international and European level as regards exclusions from patentability based on reasons of ethics and morals is presented. A critical appraisal of the case law of the Court of Justice of the European Union as regards patentability of embryonic stem cells is offered.
Keywords: ethics; scientific progress; costs of R&D; role of patents; CJEU case law